Optimizing the muscular training through alternated contraction regimes at junior female players - Vladu, L. (Journal of Physical Education and Sport, 2010)
The research purpose: is that of bettering the muscular training during the preparation process of the female junior volleyball players, adapted to the game tasks, through elaborating and confirmation of the alternate contraction regimes programs, thus ensuring an optimal and rationalized training, with the purpose of reaching the proposed performance objectives. Conclusions: The means targeting the muscular training through alternated contraction regimes have been adapted to the objectives and requests of each preparation period. The use of the alternated contraction regimes for training purposes lead to accomplishing a superiour muscular training of the female junior volleyball players, through improving the force indicators. The elaborated muscular training programs have enclosed exercises that clearly set the number of repetitions and series, in function of the female player` capacity to deal with effort; the length of the pauses was also a preestablished element.